2016
DOI: 10.1016/j.neuron.2016.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Spatial and Feature Attention in Posterior Parietal Cortex

Abstract: Summary Lateral intraparietal (LIP) neurons encode a vast array of sensory and cognitive variables. Recently, we proposed that the flexibility of feature representations in LIP reflect the bottom-up integration of sensory signals, modulated by feature-based attention (FBA), from upstream feature-selective cortical neurons. Moreover, LIP activity is also strongly modulated by the position of space-based attention (SBA). However, the mechanisms by which SBA and FBA interact to facilitate the representation of ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 50 publications
14
57
0
Order By: Relevance
“…Furthermore, our trained networks reproduce mixed category and match selectivity, which is evident in our neural data (Figure S2H–I) and other studies (Ibos and Freedman, 2014; Ibos and Freedman, 2016; Park et al, 2014; Rishel, 2013; Mante et al, 2013; Rigotti et al, 2013). This suggests that a large portion cortical neurons and model neurons participate in more than one computation.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, our trained networks reproduce mixed category and match selectivity, which is evident in our neural data (Figure S2H–I) and other studies (Ibos and Freedman, 2014; Ibos and Freedman, 2016; Park et al, 2014; Rishel, 2013; Mante et al, 2013; Rigotti et al, 2013). This suggests that a large portion cortical neurons and model neurons participate in more than one computation.…”
Section: Resultssupporting
confidence: 82%
“…First, the existence and abundance of mixed selectivity neurons (Ibos and Freedman, 2014; Ibos and Freedman, 2016; Mante et al, 2013; Park et al, 2014; Raposo et al, 2014; Rigotti et al, 2013; Rishel, 2013) and the time-varying selectivity for task-relevant variables at both single-neuron (Brody et al, 2003a; Jun et al, 2010; Shafi et al, 2007) and population levels (Machens, 2010; Crowe et al, 2010; Meyers et al, 2008; Wohrer et al, 2013) have sparked a debate on the dynamical nature of working memory (Druckmann and Chklovskii, 2012; Goldman, 2009; Sarma et al, 2016; Savin and Triesch, 2014; Singh and Eliasmith, 2006). Since the model captures all these features, it is possible now to pinpoint the working memory dynamics that give rise to these patterns of selectivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some differences in timing of neuronal responses during spatial versus feature attention tasks have been observed [48, 50] but see [58]. However, most studies describe additive effects of spatial and feature attention and many suggest separate mechanisms [4, 51, 55]. Relationships between feature attention modulation and individual neuronal selectivity have only been explored in a handful of studies with somewhat conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly plausible given the presence of feature selective neurons, in LIP, e.g. cells with selective responses to differently orientated lines (9)(10)(11)(12). We have also recently shown that LIP contains two groups of neurons having distinctly different responses to the stimuli in our DMS task, which occur during different parts of the delay period between the stimulus pair (12).…”
Section: One Sentence Summarymentioning
confidence: 69%